Devins sur le pas de la porte : notes pour une anthropologie visuelle du seuil en Galice - Anxo Fernández Ocampo (Conserveries Mémorielles)
This article is the result of an experience at the crossroads of traductology and visual anthropology. It highlights the capacity of the domestic thresholds to cope with the alien by the means of traces or objects that are invested with an “exoticising” value, either because these traces or these objects are identitary representations of the past, or because they embody the other and the elsewhere. The field of exploration is rural and extends over several hamlets of a same community of North East Galicia. In the methodology used here, the observer substitutes himself to the passer-by and the visitor in order to take pictures of the thresholds and the signs, namely on the leaf of the doors which are authentic supports of scripture. He also attempts to engage in dialogue with the inhabitant, and ventures to cross the threshold: this interaction validates the experience and creates a harmony between the technical constraints and the epistemological frame of research. This is how many phenomena are analyzed, be it the cultural and scriptural acceptability of a foreign name, the setting of objects that engage in a dialogue with the passer-by or the arrangement of sacred icons on domestic altars. As threshold is an exceptional translating space, this article reveals the role of every inhabitant as a negotiator of alterity, intermediate of trans-cultural operations, and to extend descriptive research methods to the reading of threshold spaces and finally, to the study of popular practices of signification.